Soft sediment deformation features in Dauki Fault region : evidence of paleoearthquakes, Shillong Plateau, NE, India - Lakshmi, B.V.; Gawali, Praveen B. (My University, 2022)
The northeastern region (NER) of India has several complex regional geological structures, out of which the Dauki fault (DF) is a prominent one. The E–W trending reverse DF, which is inferred to go through the southern margin of Shillong Plateau (SP), has played major role in the regional deformation of the adjoining areas and was believed to be active during the Late Quaternary time. Previous paleoseismological studies conducted on the eastern and western part of the DF, Bangladesh, revealed that the fault ruptured in AD 849–920 and AD 1548, respectively. However, there were no studies on the DF from southern side of the SP, India. For the frst time, from Indian side, soft sediment deformation structures (SSDS) are reported from fve trenches in and around the DF zone, SP. Close to the Dauki village, fve trenches in the eastern part of the DF, SP, show micro faulting, sand dykes, disturbed strata, and water escape structures. The detailed nvestigation of SSDS indicates that the origin of deformation is seismic trigger. The 14C AMS dating of deformation structures generated by earthquakes suggests three seismic events occurred between 130 and 920 year BP, 5415 to 9140 year BP, and at about 4285 year BP. This study confrms that DF is indeed active, at least, since the mid-Holocene. More trenching and dating of seismically induced deformation features are needed to accurately calculate the recurrence interval of signifcant earthquakes that can strike the fast-expanding urban areas in India and Bangladesh.
Keywords: Earthquake, Dauki fault, Soft sediment deformation, Micro faulting, 14C AMS dating, Mid-Holocene